Goss's bacterial wilt and leaf blight of corn in Canada – disease update. Issue 4 (2nd October 2018) - Harding, Michael W.; Jindal, Krishan; Tambong, James T.; Daayf, Fouad; Howard, Ronald J.; Derksen, Holly; Reid, Lana M.; Tenuta, Albert U.; Feng, Jie
Abstract: Goss's bacterial wilt and leaf blight, caused by Clavibacter nebraskensis (syn. C. michiganensis subsp. nebraskensis ), is a serious disease of corn. It is not new to North America, but in 2006, the number of outbreaks increased and the pathogen was reported in areas of the USA and Canada where it had not previously been found. The disease is increasing in distribution and severity and new areas such as the northern Prairies may be at higher risk as corn production acreage rises. Therefore, Goss's wilt monitoring and subsequent management should be priorities in areas where the disease has appeared relatively recently, such as the Canadian Prairie provinces. This update summarizes the current status of Goss's bacterial wilt and leaf blight in Canada including its geographic distribution as determined through recent monitoring activities and new detection methods. It also discusses current knowledge regarding pathogen biology, disease development, epidemiology and management.